Monetary policy shocks, set-identifying restrictions, and asset prices: A benchmarking approach for analyzing set-identified models - Gábor B. Uhrin; Helmut Herwartz (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2016)
A central question for monetary policy is how asset prices respond to a monetary policy shock. We provide evidence on this issue by augmenting a monetary SVAR for US data with an asset price index, using set-identifying structural restrictions. The impulse responses show a positive asset price response to a contractionary monetary policy shock. The resulting monetary policy shocks correlate weakly with the Romer and Romer (2004) (RR) shocks, which matters greatly when analyzing impulse responses. Considering only models with shocks highly correlated with the RR series uncovers a negative, but near-zero response of asset prices.
Keywords: C32; E44; E52; 330; monetary policy shocks; asset prices; sign restrictions; zero restrictions; set identification; structural VAR models